Al-Baladhuri and writing history (Journal of the College of Basic Education, 2022)
At the beginning of the third century AH, literary authorship was active in general due to a new incentive generated by the high levels of material culture and the development of paper, as the first factory for it was established in Baghdad in the year 178 AH. The second half of the third century AH witnessed the emergence of historians who were not limited by a school or direction. From the materials of "The Prophet's Biography", from the books of the "Akhbaris", from genealogical books and other sources